Kekerasan Rumah Tangga Dalam Film Televisi Sinema Indosiar (Analisis Isi Kekerasan dalam Rumah Tangga Dalam Film Televisi Sinema Indosiar Periode 27 Mei Hingga 2 Juni 2014) - Setyaningrum, Ratna; , Fajar Junaedi, M.Si; , Nur Latifah Umi Satiti, M.A (2015)
Case of Domestic Violance in Indonesia still be an interesting phenomena to be discussed. As A mirror of situatipn social life, media often to shows the impressions that tell abaut daily live. Film Television (FTV) is one the product of the mass media that they are often showing of domestic violence scanes. That is consist of negative educations. The porpuse of this research is to calculate culate the frequency of trend domestic violence scane. That used the sistem of camera, and the comparison between the perpetrator with the victim in the conduct of domestic violence in Indoisar Cinemas period on May 27 to June 2, 2014. Use the content analyze method, dismethod technique is to difine the content of real communications in objective, systematic, and kuantitatif. The result is the scane of domestic violence is which often arises is psychological violence amounted 85.1% or as much as 97 variables. In this case, the most frequent of violence arises is a growl or snarl that is equal to 31.6% . In broadcast, the use of camera system most frequently arises is a Close Up, amounting to 34.2% or as much as 39 variables.